Gambaran Faktor-Faktor Ibu Bersalin Dalam Memilih Pertolongan Persalinan Dengan Bantuan Dukun Bayi Di Puskesmas Wonosegoro II Boyolali - Sujatmoko, Sujatmoko; , Sulastri, S.Kp, M.Kes; , Ns. Arief Wahyudi Jadmiko, M.Kep (2016)
Decline in maternal rate and the infant mortality rate in rural or remote areas can not be as expected the government, because in rural or remote communities in general they are still many who do not give birth at a health facility to another. Remote communities include communities in mountainous areas and difficult to reach with a low educational background, socioeconomic weak, and access to health services is not good, so there are many pregnant women who delivered at non-health workers. This study aims to describe the factors of pregnant women in choosing aid delivery with the help of infant shaman in the working area UPTD Boyolali district health center Wonosegoro II. This research is descriptive. Sample study was 47 pregnant women who use birth help of infant shaman with proportional random sampling technique. Collecting data using questionnaires were analyzed using descriptive test. Research shows that (1) the geographic location of the decision birth mothers in selecting deliveries in personnel non-health or infant shaman are close enough and easy, (2) most of the education level of maternal is SD, (3) the majority of cultures mother maternity is less support to health services, (4) support the family to do deliveries to non-health workers or infant shaman are mostly good, and (5) socio-economic conditions of the respondents largely moderate category. The conclusions of the fifth picture of the most dominant factor influencing family support birth mothers to choose aid delivery to infant shaman. Keywords: deliveries with infant shaman, geographical location, education, cultures, family support, social economy.